2003
DOI: 10.1034/j.1600-0765.2003.00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcification of degenerating tissues in the periodontal ligament during tooth movement

Abstract: This calcification of the degenerating tissues is a self-defense response of the living body to prevent direct contact between alveolar bone and the tooth root during compression of the PDL, so preventing friction between them and the development of ankylosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Group 2 consisted of 5 rats, and they wore orthodontic wire (experimental group). Upper first molars of the experiment groups were moved palatally (0.1 N) with the fixed appliance (Nakamura et al, 2003). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Group 2 consisted of 5 rats, and they wore orthodontic wire (experimental group). Upper first molars of the experiment groups were moved palatally (0.1 N) with the fixed appliance (Nakamura et al, 2003). …”
Section: Methodsmentioning
confidence: 99%
“…Cells in the PDL are subjected to continuous mechanical strain and are forced to adapt to the new environment by synthesis and secretion of several cytokines and growth factors (Arai et al, 2010; Baba et al, 2011; Saito et al, 1991; Tsuge et al, 2016). As a result, reconstruction of the PDL and alveolar bone occur both in the tension and compression zones of the PDL (Nakamura et al, 2003; Shimpo et al, 2003; Takahashi et al, 2003, 2006). However, the detailed mechanisms of the cellular response in reconstruction of the PDL and alveolar bone have not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it has been suggested that ALP plays an important role in the supply of phosphoric acid in calcification (Mayahara 1980), or is a kind of calciumbinding protein (Bernard et al 1986). ALP in the periodontal ligament was localized in the plasma membrane of the fibroblasts and collagen fibers, but none of the periodontal ligament calcifies except in pathological conditions (Nakamura et al 2003). ALP in the fibroblasts and collagen fibers may regulate the local concentration of phosphate or calcium.…”
Section: Discussionmentioning
confidence: 98%
“…Continuous orthodontic force on the tooth is considered to be a kind of physical stress loaded to the periodontal ligament (PDL) (Macapanpan et al 1954;Reitan 1960;Kvam 1969;Azuma 1970;Rygh 1972Rygh , 1974Vandevska-Radunovic et al 1994;Nakamura et al 1996Nakamura et al , 2003. This stress causes gradual compression of the PDL, which leads to circulatory disturbance such as ischemia and hypoxia in the pressure zone of the PDL at early stages of tooth movement.…”
Section: Introductionmentioning
confidence: 98%